Chronic Systemic Inflammation Exacerbates Neurotoxicity in a Parkinson's Disease Model. (13th January 2020) - Ugalde-Muñiz, Perla; Fetter-Pruneda, Ingrid; Navarro, Luz; García, Esperanza; Chavarría, Anahí
Abstract : Systemic inflammation is a crucial factor for microglial activation and neuroinflammation in neurodegeneration. This work is aimed at assessing whether previous exposure to systemic inflammation potentiates neurotoxic damage by the neurotoxin 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) and how chronic systemic inflammation participates in the physiopathological mechanisms of Parkinson's disease. Two different models of systemic inflammation were employed to explore this hypothesis: a single administration of lipopolysaccharide (sLPS; 5 mg/kg) and chronic exposure to low doses (mLPS; 100  μ g/kg twice a week for three months). After three months, both groups were challenged with MPTP. With the sLPS administration, Iba1 staining increased in the striatum and substantia nigra, and the cell viability lowered in the striatum of these mice. mLPS alone had more impact on the proinflammatory profile of the brain, steadily increasing TNF α levels, activating microglia, reducing BDNF, cell viability, and dopamine levels, leading to a damage profile similar to the MPTP model per se . Interestingly, mLPS increased MAO-B activity possibly conferring susceptibility to MPTP damage. mLPS, along with MPTP administration, exacerbated the neurotoxic effect. This effect seemed to be coordinated by microglia since minocycline administration prevented brain TNF α increase. Coadministration of sLPS with MPTP only facilitated damage induced by MPTP without significant change in the inflammatory profile. These results indicate that chronic systemic inflammation increased susceptibility to MPTP toxic effect and is an adequate model for studying the impact of systemic inflammation in Parkinson's disease.